Multivariability of Rights in the Structure of Corporate Legal Relations - KOSTRUBA, Anatoliy V.; LUKIANOV, Dmytro (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).13, 2019)
The research is devoted to the study of the structure of corporate legal relations, establishing the mechanism of their formation. Legal relations as a form of social relations are in constant development due to the activity of social ties in society. As a result, new types of social interaction emerge and develop that require an appropriate legal form of ordering. Such ordering is self-regulated by the participants of the respective relations in the process of accumulation of property, non-property components, organizational and so on. The study found that the formation of corporate legal relations is the result of a combination of property, non-property and organizational   components. The organizational   component of corporate relations is to streamline the activities of individuals in the process of combining their efforts at the stage of emergence of such relationships, as well as to streamline this activity of participants in corporate relationships in the process of their implementation. It can be concluded that the proprietary nature of corporate legal relationships is conditioned by the material interest of the participants in such relationships to receive appropriate satisfaction from their participation in them. The corporation is managed through a non-property segment.